A "Confounded Scrape": John Herschel, Neptune, and Naming the Satellites of the Outer Solar System. (August 2019) - Case, Stephen
This paper examines John Herschel's role in establishing nomenclature for the moons of the outer solar system. Prior to the publication of Herschel's Cape Results in 1847, moons of the solar system were referred to either collectively (e.g. the Medicean stars) or by number. The common narrative is that with the discovery of additional moons around Saturn, this numbering convention became confused, causing Herschel to propose proper names for Saturn's moons in his Cape Results . An examination of Herschel's correspondence and journals, however, indicates that this new convention was likely motivated not by issues of clarity but by controversy in planetary naming brought about by the discovery of Neptune. Herschel offered mythological names for Saturn's satellites as a way to resolve this controversy, which he had helped initiate. This new naming narrative highlights Herschel's role as arbiter in the international astronomical community as well as the cultural and political background of naming conventions in the solar system.